Neu-Laxova Syndrome: An Unusual Association with Kyphosis - Amandeep KAUR; Vijayalaxmi SURANAGİ; Kamal PATİL; Hema BANNUR (Federation of Turkish Pathology Societies, 2018)
The Neu-Laxova syndrome is a rare autosomal recessive condition associated with neuro-ectodermal abnormalities and other patterns of severe malformations leading to prenatal or early postnatal lethality. Association with kyphosis is an extremely rare finding. A fetus born from a 25-year-old gravida at 30 weeks gestation was diagnosed with Dandy Walker syndrome with severe intrauterine growth restriction on ultrasonography. On post-mortem examination after termination of pregnancy, the fetus showed facial dysmorphology with microcephaly, smooth shiny skin and kyphosis. Skin histology showed hyperkeratosis, edema and increased subcutaneous fat suggestive of ichthyosis. On the basis of gross and microscopic features seen, a diagnosis of Neu-Laxova syndrome was made.